1985
DOI: 10.1002/nur.4770080405
|View full text |Cite
|
Sign up to set email alerts
|

Reducing acute confusional states in elderly patients with hip fractures

Abstract: The extent to which the incidence of postoperative acute confusional states could be reduced in elderly (greater than or equal to age 60) patients with hip fractures was tested. Interpersonal and environmental nursing interventions were carried out with 57 patients on orthopedic units in three hospitals. The incidence of confusion was reduced from 51.5% in the comparison group (n = 170) to 43.9%. Analysis that controlled for risk factors in the two groups showed the drop in incidence to be significant (p less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
3
4

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 20 publications
7
76
3
4
Order By: Relevance
“…3,4 Delirium is often not recognized, [5][6][7] and intervention benefits to date have shown to be limited. [8][9][10] Thus, prevention through identification of a high-risk group is indicated.…”
mentioning
confidence: 99%
“…3,4 Delirium is often not recognized, [5][6][7] and intervention benefits to date have shown to be limited. [8][9][10] Thus, prevention through identification of a high-risk group is indicated.…”
mentioning
confidence: 99%
“…The factors of importance may rather be the organization and treatment on the hospital ward. Williams et al (1985) showed a positive effect with increased continuity and education of the nurses. So-called active reorientation measures have proved to be valuable after open heart surgery (Budd and Brown 1974).…”
Section: Postoperative Mental Patients Impairment In Hip Fracturementioning
confidence: 96%
“…It has been noted in one third to one half of the patients on admission to hospital (Gustafson et al 1991, Ogilvie-Harris et al 1993). An equally large number of patients have been found to develop mental deterioration postoperatively (Williams et al 1985, Gustafson et al 1988. This is associated with an increased incidence of local and systemic complications (Berggren et al 1987, O'Brien et al 1993, Svensson et al 1996.…”
Section: Postoperative Mental Patients Impairment In Hip Fracturementioning
confidence: 99%
“…Для больного должно быть создано адекватное окруже-ние, с минимальным числом смен палаты и место-положения, персонала, низкой освещенностью па-латы по ночам и минимальным уровнем шума. Только в ограниченном числе исследований изучал-ся вопрос об эффективности когнитивных, эмоцио-нальных и средовых вмешательств при лечении де-лирия [55][56][57][58], но такие вмешательства стали стан-дартными рекомендациями, базирующимися на клиническом опыте, здравом смысле и отсутствии побочных эффектов [59].…”
Section: нефармакологические стратегии леченияunclassified